Hidden in Plain Sight? Corporate Strategic Litigation in the EU Emissions Trading System - Sofie Fleerackers (German Law Journal)
This Article examines how private economic actors mobilize EU law to pursue broader legal, political, economic, or societal ends. It studies the strategic nature of corporate litigation before the Court of Justice of the EU in the context of the EU Emissions Trading System, a prime illustration of neglected strategic climate litigation. Corporate cases against the ETS have so far fallen under the radar of scholarship focused on EU strategic climate litigation. Such underrepresentation is linked to a double bias in scholarship, favoring high-profile climate cases that advance public interest causes and progressive agendas. Applying a normatively open definition of strategic litigation and actor-centered methodological approach, the Article brings to light features of corporate strategic litigation in EU law which otherwise go unseen. It offers empirical observations into boundary-testing behavior by private economic actors and the notion of a private generalizable interest, untangling strategic climate litigation by private economic actors as overlooked proponents in Court. The Article finally distinguishes a selection of legal strategies through which corporate actors mobilize EU law, such as instances of coordinated litigation; futile and seemingly routine challenges initiated before the Court to test judicial waters; and the use of litigation as a political advocacy tool.